Rhodium(iii) complexes with isoquinoline derivatives as potential anticancer agents: in vitro and in vivo activity studies. Issue 30 (10th July 2019) - Khan, Taj-Malook; Gul, Noor Shad; Lu, Xing; Kumar, Rajesh; Choudhary, Muhammad Iqbal; Liang, Hong; Chen, Zhen-Feng
Abstract : Two rhodium complexesRh1 andRh2 with isoquinoline derivatives were synthesized and characterized. Abstract : Two rhodium complexesRh1 andRh2 with isoquinoline derivatives were synthesized and characterized. Both complexes displayed strong anticancer activity against various cancer cells and low cytotoxicity against non-cancer cells. These complexes triggered apoptosis via mitochondrial dysfunction that increased the levels of ROS and Ca 2+ and released cytochrome C which ultimately activated caspases and the apoptosis pathway. The different biological activities ofRh1 andRh2 could be associated with the presence of methoxy substituents on the ligands. In vivo studies showed thatRh1 effectively inhibited tumor growth in a T-24 xenograft mouse model with a less adverse effect than cisplatin. Overall, Rh1 andRh2 induced apoptosis via mitochondrial pathways and could be developed as effective anticancer agents.